Making government manageable : executive organization and management in the twenty-first century - Stanton, Thomas H.; Ginsberg, Benjamin (Baltimore : Johns Hopkins University Press, 2004)
This book argues that the organization of government is critical to the success of government and gives practical examples and principles of manageable and successful government.
Includes bibliographical references and index.
oif 27/10/2015
Loans
Keywords: Administrative agencies; United states